Checklist to combat bribery launched - Ong, Han Sean (The Star Publications (M) Berhad, 2017)
KUANTAN: Yayasan Pahang and Universiti Malaysia Pahang (UMP) have set up an Anti-Bribery Management System Checklist (ABMSC) in an effort to combat corruption.